A biopolymer‐based 3D printable hydrogel for toxic metal adsorption from water. Issue 5 (15th March 2019) - Appuhamillage, Gayan A; Berry, Danielle R; Benjamin, Candace E; Luzuriaga, Michael A; Reagan, John C; Gassensmith, Jeremiah J; Smaldone, Ronald A
Abstract: Herein, we describe a 3D printable hydrogel that is capable of removing toxic metal pollutants from aqueous solution. To achieve this, shear‐thinning hydrogels were prepared by blending chitosan with diacrylated Pluronic F‐127 which allows for UV curing after printing. Several hydrogel compositions were tested for their ability to absorb common metal pollutants such as lead, copper, cadmium and mercury, as well as for their printability. These hydrogels displayed excellent metal adsorption with some examples capable of up to 95% metal removal within 30 min. We show that 3D printed hydrogel structures that would be difficult to fabricate by conventional manufacturing methods can adsorb metal ions significantly faster than solid objects, owing to their higher accessible surface areas. © 2019 Society of Chemical Industry Abstract : Here we report a 3D printable, bio‐based, hydrogel that is capable of removing toxic metals from aqueous solutions with improved adsorption kinetics compared to non‐3D‐printed shapes.